2008
DOI: 10.1002/cjoc.200890215
|View full text |Cite
|
Sign up to set email alerts
|

n‐Butane Monomolecular Cracking on Acidic Zeolites: A Density Functional Study

Abstract: Density functional theory was used to study monomolecular cracking reaction of n-butane on acidic zeolite. Geometry optimizations of the local structures of the species reacting with the zeolite were carried out by using the 5T cluster model at the B3LYP/6-311+G(3df,2p)//B3LYP/6-31G(d) level. In this work, the deprotonation modes of two different order C atoms in n-butane cracking on H-ZSM-5 were explored in detail by the density functional theory. The calculated activation barriers at the B3LYP/6-311+G(3df,2p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 44 publications
4
14
0
Order By: Relevance
“…Several studies have also reported free energies or entropies of activation. 3,5,6,11,23,24,32 Good agreement between theory and experiment has been reported for ΔS ⧧ int for alkane cracking in MFI using a composite hindered rotor approach adapted from that reported by Grimme 33 to account for internal rotations. 11 However, no previous studies have attempted to describe the activation entropy for dehydrogenation.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…Several studies have also reported free energies or entropies of activation. 3,5,6,11,23,24,32 Good agreement between theory and experiment has been reported for ΔS ⧧ int for alkane cracking in MFI using a composite hindered rotor approach adapted from that reported by Grimme 33 to account for internal rotations. 11 However, no previous studies have attempted to describe the activation entropy for dehydrogenation.…”
Section: Introductionmentioning
confidence: 74%
“…We also note that theoretical investigations of the effects of active site environment on kinetics have been very limited. While a few studies have investigated the effects of induced changes in acidity, 14,24,29 only three of the aforementioned studies have investigated the effects of structural confinement. 5,20,22 Sharada et al have reported that activation energies for n-butane cracking and dehydrogenation differ for intersection and sinusoidal channel sites of MFI.…”
Section: Introductionmentioning
confidence: 99%
“…However, these authors attributed such differences to differences in acidity among zeolites. It is noted that differences in acidity, if present, would be expected to influence the kinetics of monomolecular activation of alkanes based on a number of experimental and theoretical studies, a subject that has recently been reviewed by Boronat and Corma and by Derouane et al . This raises the issue of whether the acidity of protons is correlated with zeolite structure and confinement, since this Minireview is focused primarily on the effects of structure and confinement on alkane cracking and dehydrogenation kinetics.…”
Section: Experimental Studies Of Reaction At Brønsted Acid Sitesmentioning
confidence: 99%
“…[60] However,t hese authors attributed such differencest od ifferences in acidity among zeolites. It is noted that differences in acidity,i fp resent, would be expected to influence the kinetics of monomolecular activation of alkanes based on an umber of experimental [5,6,61] and theoretical [5,7,[62][63][64][65] studies, as ubject that has recently been reviewed by Boronat and Corma [66] and by Derouane et al [49] This raises the issue of whether the acidity of protons is correlated with zeolite structure and confinement, since this Minireview is focused primarily on the effectso fs tructure and confinement on alkane cracking and dehydrogenation kinetics. Several studies have concluded that the acidity is independento ft he zeolite structurea nd the locationo ft he acid sites, [5][6][7] buti sd ependent on the heteroatom (Al, B, Ti) [5] and on the concentration of framework Al atoms for lowv alues of the Si/Al ratio [67][68][69] for which the acidity is lower as ar esult of the presence of Al next-nearest-neighbor pairs.…”
Section: Effect Of Zeolite Topologymentioning
confidence: 99%
See 1 more Smart Citation